2018
DOI: 10.21037/jtd.2017.12.123
|View full text |Cite
|
Sign up to set email alerts
|

Screening for early stage lung cancer and its correlation with lung nodule detection

Abstract: Currently, the most effective way of reducing lung cancer mortality is early diagnosis of lung cancer. The National Lung Screening Trial has proved the efficacy of lung cancer screening using lowdose computed tomography to reduce lung cancer mortality. However, many questions remain surrounding lung cancer screening implementation, among which include how to select the optimal risk population, the personalized screening interval based different levels of risk, methods to improve diagnostic discrimination betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 119 publications
0
19
0
Order By: Relevance
“…Other studies have found that benign results of cancer workup are associated with distress and decreased quality of life comparable to that observed in patients diagnosed with malignancy, and it is plausible that the uncertainty of possible a false‐negative diagnosis induces increased levels of anxiety. (Brodersen & Siersma, 2013; Lemonnier et al, 2011; Pelletier et al, 2012; Qian et al, 2018; Rasmussen et al, 2015) Both newly diagnosed benign disease ( e . g .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that benign results of cancer workup are associated with distress and decreased quality of life comparable to that observed in patients diagnosed with malignancy, and it is plausible that the uncertainty of possible a false‐negative diagnosis induces increased levels of anxiety. (Brodersen & Siersma, 2013; Lemonnier et al, 2011; Pelletier et al, 2012; Qian et al, 2018; Rasmussen et al, 2015) Both newly diagnosed benign disease ( e . g .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, different concurrent factors have widened the indications for surgical resection of lung nodules. The widespread use of radiological imaging, as is happening with the implementation of lung cancer screening programs, has multiplied the findings of undetermined pulmonary nodules in asymptomatic patients (23). Developments in treatments for advanced lung cancer suggest the need for histological samples to guide the therapy (24).…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of asymptomatic cancer patients, during routine clinical practice, are not diagnosed at the right time. But by the time when the subsequent results come in for diagnostic purposes, nearly 70% of NSCLC patients have reached an advanced stage, either locally or have metastasised to other organs [15]. In other words, a possible solution to the survival of lung cancer patients could be an early-warning indicator, the need of the hour.…”
Section: Introductionmentioning
confidence: 99%